PERAN GURU DALAM MEMOTIVASI BELAJAR BAHASA ARAB SISWA MADRASAH TSANAWIYAH - Syukron Al-Itmam; Moch. Hasyim Fanirin; Iis Susiawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Arabic language learning in Indonesian madrasahs often faces challenges as it is perceived as difficult and less relevant to students’ daily lives, making learning motivation a key factor for success. This study aims to analyze the role of teachers in motivating eighth-grade students at MTs Ma’had Al-Zaytun and to identify the strategies used to enhance motivation in Arabic learning. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation involving three Arabic teachers and fifteen students selected purposively. The findings reveal that teachers act not only as instructors but also as role models and motivators by implementing interactive learning media, providing rewards, and engaging in empathetic communication. These strategies foster both intrinsic and extrinsic motivation, build students’ confidence, and encourage active participation in class. The study concludes that teachers play a crucial role in shaping students’ motivation to learn Arabic in a boarding school environment. The results highlight the need to strengthen teachers’ competencies in designing adaptive and communicative learning strategies aligned with students’ needs, while also contributing academically to the development of motivation theories in foreign language learning within Islamic education.